Effect of submerged combustion evaporation on Cd complexation potential of organic matter in municipal solid waste landfill leachate. (December 2020) - Zhang, Lingyue; Wang, Xinyue; Yue, Dongbei
Abstract: Despite the strong ability for complexation of heavy metals, a high amount of humic substances (HS) is always contained in membrane retentate from municipal solid waste landfill leachates treatment processes. Submerged Combustion Evaporation (SCE) can be used to effectively concentrate the membrane retentate. However, the impact of the SCE treatment on HS complexation capacity is still unclear. Since cadmium (Cd) plays a vital role in the pollution of soil and food, this study investigated the influence of the SCE treatment on the Cd complexation potential of leachate HS. Specific effects and complexation properties on Cd complexation of leachate HS before and after the SCE treatment were demonstrated using the Non-Ideal Competitive Adsorption model. The results showed that the Cd complexation capacity of carboxyl sites increased from 3.76 to 4.65 mol/kg-Total Organic Carbon (TOC) after the SCE treatment, which agreed with the stoichiometric number of proton binding sites. Moreover, characterization results indicated that SCE increased the affinity of HS for Cd by enhancing the overall aromaticity of HS (E2 :E4 from 9.8 to 9.3), dominantly due to the humic acid contribution. By modeling the practical Cd remediation scenarios, the enhanced Cd complexation performance of HS after SCE treatment was observed even at low pH values (pH = 5) or insufficient TOC content (TOC = 50 mg/L). Graphical abstract: Image 1 Highlights: Cd complexation capacity of leachate HS increases after SCE treatment. The complexation parameters of HS increase from 1.38 to 1.61 after SCE. Increased aromaticity degree of HS leads to the enhanced complexation capacity. The aromatization of HA increased by 0.5% is a dominated factor. pH value plays a significant role at low level of TOC (50 mg/L). Abstract : Main finding:Complexation performance of leachate humic substances is enhanced after Submerged Combustion Evaporation. Increased aromaticity degree dominates the enhancement.